Intervention in emotional education. Effects on the emotional competence of primary and secondary school students - Berastegui-Martínez, Jon; de la Caba-Collado, María Ángeles; Pérez-Escoda, Núria (Revista Complutense de Educación, 2024)
INTRODUCTION. Despite the fact that the Organic Law 3/2020, on education, explicitly recognizes emotional education as a compulsory subject in all compulsory education, only 5% of schools currently include emotional education in their educational project (IDIENA, 2021). METHOD. The aim of this research was to evaluate the impact of an intervention in emotional education on the emotional competence of students in three different grades: 6th year of Primary, 2nd and 4th year of Secondary. A total of 142 students participated, 66 belonging to the experimental group and 77 to the control group. A quasi-experimental pretest-posttest design was used, with a mixed methodology control group. The following instruments were used: the emotional development questionnaires, CDE (9-13) and CDE-SEC; and a student notebook. RESULTS. Participating students experienced significant improvements in total emotional competence, as well as in emotional awareness, emotional autonomy and social competence. Among the three programmes applied, the one developed in the 2nd year of Secondary School was the most effective in the development of these competences. There were no significant differences in the effects of the programme according to the sex of the participants. DISCUSSION. This research provides evidence of the benefits of emotional education in the development of emotional competences at three key moments in the students’ school life.